Determinants factor of passengers’ propensity to utilise e-hailing services in Kota Kinabalu, Sabah - Azwa Safiqah Darawati; Mohd Azizul Ladin (UTHM, 2024)
In the realm of public transportation, e-hailing services have emerged as a prominent mode of transportation in recent years. This study aims to elucidate the complex relationships between four key constructs, namely safety features, fare, ease of usage, and accessibility, in shaping user inclination towards the adoption of e-hailing services. Using the Stated Preference Survey (SPS) method, a meticulously designed online questionnaire was administered to three hundred respondents in Kota Kinabalu. Employing partial least squares-structural equation modelling for analysis, the results highlight the significance of ease of usage and accessibility as robust predictors influencing Kota Kinabalu residents' preference for using e-hailing services. The safety aspect displays notable disparities based on gender, as male and female consumers possess contrasting perspectives regarding the degree of protection provided by e-hailing services. In contrast, the concept of price value has a restricted ability to forecast user propensity, as surge pricing was universally enforced during peak hours in all e-hailing services. The study's findings provide useful insights for e-hailing businesses, indicating strategic enhancements in service delivery to guarantee customer comfort and safety, thereby increasing their service coverage, and attracting a wider user demographic.